Multidrug-resistant tuberculous orchiepididymitis: a brief case report - Souza, César Augusto Tomaz de; Silva, Jussemara Souza da; Correia, Ademir Silva; Rodrigues, Denise Silva (Revista do Instituto de Medicina Tropical de São Paulo, 2023)
Tuberculosis (TB) is one of the leading causes of death by infectious diseases worldwide. Multidrug-resistant tuberculosis is a growing problem, especially in countries with high TB prevalence. Although the lungs are the organs most frequently affected by this disease, Mycobacterium tuberculosis can harm any organ, including the urogenital tract, causing extrapulmonary tuberculosis, which leads to a challenging diagnosis and consequent treatment delays. In this article, we present a case of orchiepididymitis caused by multidrug-resistant TB (MDR-TB) with a significantly delayed diagnosis, the proposed treatment according to the resistance profile, and the clinical outcomes.